Effects of Co-Administration of Lycopene and / or Zinc on Serum Electrolyte In Alloxan- Induced Diabetic Wistar Rat - A.D.T, Goji; K.A, Muhammed; J.A, Tende; I, Aisha (Journal of Medical Biomedical and Applied Sciences, 2018)
Background: The incidence of diabetes is increasing rapidly with interference in electrolytes sodium (Na+), potassium(K+) and chloride (Cl-). This work was designed to study the effects of co-administration of Lycopene and/or Zinc onSerum Electrolyte in Alloxan- Induced Diabetic Wistar Rat.Material and Methods: Healthy albino rats weighing between 150g and 200g were used. The rats were randomlyallotted into six groups, each containing five albino rats respectively. Five of the groups ( II,III IV V and VI) were inducedwith diabetes by single intraperitoneal (i.p) injection of freshly prepared in 0.1 mol/L citrate buffered solution (pH 4.5)of streptozotocin (Sigma Aldrich, St. Louis, MO, USA) at a dose of 150 mg/kg body weight. Control (vehicle) rats wereinjected with equal volume of 0.1 mol/L citrate buffer. Four days after Alloxan injection, diabetes induction was confirmedby measuring fasting blood glucose level in a tail vein blood samples using ACCU-CHEK compact plus glucometer(Roche, France). Rats with glucose level of 200 mg/dl or higher were considered as diabetic. After the induction ofdiabetes the rats were treated using the Lycopene and Zinc separately and in combination respectively according togroup daily, whereas, the other group (I) was not given any treatment and this served as the normal control, providinga baseline data.Results: The diabetic treated groups had significantly (P < 0.05) higher serum Na+ concentration than the diabeticcontrol group. The diabetic treated groups had significantly (P < 0.05) lower serum K+ concentration than the diabeticcontrol. Also, the diabetic treated groups had significantly (P < 0.05) higher Clô concentration than the diabetic controlgroup. The diabetic treated group had significantly (P < 0.05) lower HCO3ô concentration than the diabetic controlgroup. The diabetic treated groups had significantly (P < 0.05) lower serum urea concentration when compared to thediabetic control. The diabetic treated groups showed significantly (P < 0.05) decrease in serum creatinine concentrationas compared to the diabetic control group.Conclusion: These anomalies were all ameliorated to about normal values after four weeks of treatment withLycopene+Zinc. This suggests the synergistic beneficial effects of lycopene acid and zinc against alloxan-induceddiabetes in Wistar Rats.